TikTok Algorithms and the Escalation of Interfaith Conflict in Indonesia - Jamil, Muhamad; Khusairi, Abdullah (Analisa: Journal of Social Science and Religion, 2025)
This study examines the escalation of interreligious conflict on the TikTok platform, which is increasingly dominating social interaction in Indonesia. By analysing five live videos related to religious conflict (broadcast between January 2023 and December 2024) and 853,513 Indonesian-language comments through thematic coding and sentiment classification, it was found that TikTok's algorithm plays a significant role in reinforcing ideological polarization. Content nuanced with religious conflict generated an average of 3.5 times more comments, and videos containing negative emotions were shared four times more often than neutral or positive content. This digital conflict often spilled over into the real world, triggering police intervention. The response of law enforcement officers was generally reactive, unable to mitigate the conflict early. These findings emphasize the need for strategic collaboration between digital platforms, law enforcement officials, and civil society to promote digital literacy and ethical interfaith dialogue. This collaboration is expected to prevent ideological segregation and create a more constructive interaction space in the digital era.